Dampak Perubahan Titik Batas Di Pulau Sebatik Perbatasan Antara Indonesia Dan Malaysia Dalam Perspektif Prinsip Uti Prossidentis - Maria Viviana Ero Payon; Maria Fatima Kartika Mao Foju; Yohanes Arman (Pusat Riset dan Inovasi Nasional, 2023)
Sebatik Island is one of the 92 outermost small islands located in North Kalimantan province and directly adjacent to neighboring Malaysia, Malaysia. In 2011, the Sebatik Region was split again into five Districts, namely Sebatik District, West Sebatik District, East Sebatik District, North Sebatik District, and Central Sebatik District. The strategic location which is on the border of Indonesia and Malaysia as well as the potential for abundant natural resources makes Sebatik Island a cross-country strategic area. However, behind the various potentials it has, Sebatik Island has various problems, especially in the management of development and increasing the social resilience of the region. Social resilience on Sebatik Island can be realized through a power that synergizes with one another both in political, social, economic and natural resource aspects. Social resilience in the community is also highly dependent on a number of assets or potential. From these problems and problems, the researcher made a formulation of the problem, namely what is the impact of changing the boundary points on Sebatik Island on the border of Indonesia and Malaysia in the perspective of the Uti Prossidentis principle. With the aim of this writing is to analyze and find out about the impact of changing the boundary points on Sebatik Island on the border of Indonesia and Malaysia in the perspective of the Uti Prossidentis principle. The type of research conducted in this writing is descriptive research, meaning that the author tries to describe the problems that occur in the border area between Indonesia and Malaysia related to the point of change of the boundary point between Indonesia and Malaysia on Sebatik Island. In this matter, even though the governments of the two countries, Indonesia and Malaysia, have made various efforts both technically in the field and in border areas, especially at the boundary point on Sebatik Island, North Kalimantan, in the process of these efforts, the two countries, Indonesia and Malaysia, must involve academics. to support the quality of preparation and implementation strategies that will later be carried out by the relevant government. So that there is good and structured coordination between Ministries and Institutions, both central Institutions and Regional Institutions.